2017
DOI: 10.3892/ol.2017.7316
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiles during galectin‑9‑induced apoptosis of pancreatic cancer cells

Abstract: Abstract. Pancreatic cancer is the eighth-leading cause of cancer-associated mortality in males and the ninth-leading cause in females worldwide. Even when diagnosed early enough to be potentially resectable, the prognosis of invasive pancreatic cancer is poor. Galectin-9 (Gal-9) is a tandem-repeat type galectin that has recently been demonstrated to possess an anti-proliferative effect on cancer cells. Therefore, the present study evaluated the effects of Gal-9 on the proliferation of human pancreatic cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Whereas high galectin-9 expression was associated with reduced survival in lung cancer, increased expression was associated with improved survival in hepatocellular carcinoma, gastric and colorectal cancer and also with a low metastatic potential in breast cancer [17][18][19][20][21]. Notably, in pancreatic cancer cells galectin-9 has been shown to induce apoptosis [22]. However, galectin-9 had no significant effect on AsPC-1 cell proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas high galectin-9 expression was associated with reduced survival in lung cancer, increased expression was associated with improved survival in hepatocellular carcinoma, gastric and colorectal cancer and also with a low metastatic potential in breast cancer [17][18][19][20][21]. Notably, in pancreatic cancer cells galectin-9 has been shown to induce apoptosis [22]. However, galectin-9 had no significant effect on AsPC-1 cell proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Another possible explanation involves Gal-9 and its capability of inducing apoptosis. It is reported that addition of recombinant Gal-9 induced apoptosis of various malignant cells, such as hematological malignant cells ( Kobayashi et al, 2010 , 2015 ), melanoma cells ( Kageshita et al, 2002 ; Wiersma et al, 2012 ) and gastrointestinal cells ( Tadokoro et al, 2016 , 2017 ; Okura et al, 2018 ). Further experiments performed in mouse models of leukemia ( Kobayashi et al, 2010 ), myeloma ( Kuroda et al, 2010 ) and hepatobiliary carcinoma ( Fujita et al, 2015 ; Tadokoro et al, 2016 ) have demonstrated that treatment with recombinant Gal-9 prevents tumor progression by inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited number of studies about galectin-4 and galectin-9, their biological behaviours and underlying mechanisms in malignancies still remain controversy. Galectin-9 was found to suppress the proliferation of pancreatic cancer cell lines, and metastatic liver cancer cell lines [55, 56]. Conversely, higher serum galectin-9 was observed in PDAC patients [57].…”
Section: Discussionmentioning
confidence: 99%